2018
DOI: 10.5114/wiitm.2018.75845
|View full text |Cite
|
Sign up to set email alerts
|

Is the laparoscopic approach for rectal cancer superior to open surgery? A systematic review and meta-analysis on short-term surgical outcomes.

Abstract: IntroductionOver the past years the incidence of colorectal cancers has increased worldwide. Currently it is the most common gastrointestinal malignancy worldwide. The laparoscopic approach has become the gold standard for surgical treatment. However, a recently published meta-analysis showed no difference in short- and long-term oncological outcomes of laparoscopy for treating rectal cancer.AimTo assess current literature on short-term outcomes of rectal cancer treatment using laparoscopic surgery in comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 37 publications
(49 reference statements)
0
18
0
1
Order By: Relevance
“…Laparoscopic surgery is an approved technique in colorectal cancer treatment. Lower rates of perioperative complications and at least equal oncological results have been proven in randomised controlled trials and confirmed with meta-analyses [ 1 , 2 ]. Despite technical improvements to abdominoperineal resection [ 3 ], over the last two decades there has been a significant shift in types of resections performed for rectal cancer treatment [ 4 ].…”
Section: Introductionmentioning
confidence: 83%
“…Laparoscopic surgery is an approved technique in colorectal cancer treatment. Lower rates of perioperative complications and at least equal oncological results have been proven in randomised controlled trials and confirmed with meta-analyses [ 1 , 2 ]. Despite technical improvements to abdominoperineal resection [ 3 ], over the last two decades there has been a significant shift in types of resections performed for rectal cancer treatment [ 4 ].…”
Section: Introductionmentioning
confidence: 83%
“…Colorectal cancer (CRC) is the third most common cancer and the fourth most common cause of cancer‐related deaths worldwide . About athird of all large bowel cancers originate in the rectum, and are the most common malignant tumors in younger individuals .…”
Section: Introductionmentioning
confidence: 99%
“…This result is comparable to those found in the literature that show that laparoscopic rectal surgeries present a shorter hospitalization period compared to open surgeries. [ 1 , 2 , 4 , 7 , 9 , 11 14 , 21 , 24 ]…”
Section: Discussionmentioning
confidence: 99%